2022
DOI: 10.3390/ijerph191710825
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Effective Intravesical Therapies on Quality of Life in Patients with Non-Muscle Invasive Bladder Cancer: A Systematic Review

Abstract: Background: Conventional and newly emerged intravesical modalities have demonstrated prophylactic effectiveness that may improve quality of life (QoL) in non-muscle invasive bladder cancer. The purpose of this study is to analyze existing QoL evidence in patients receiving any form of intravesical therapy. Methods: A PubMed search without time restriction was conducted to identify all relevant studies in accordance with the PICOT question. Additionally, a search was also performed in the Cochrane library datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
(192 reference statements)
1
1
0
Order By: Relevance
“…The finding of relative stability of GH and PF during the course of the study is similar to that reported by Catto et al 23 and described by others 24,25 for BCG monotherapy, suggesting combination N-803 plus BCG intravesical therapy is at least as tolerable as treatment with BCG alone.…”
Section: Discussionsupporting
confidence: 90%
“…The finding of relative stability of GH and PF during the course of the study is similar to that reported by Catto et al 23 and described by others 24,25 for BCG monotherapy, suggesting combination N-803 plus BCG intravesical therapy is at least as tolerable as treatment with BCG alone.…”
Section: Discussionsupporting
confidence: 90%
“…The urinary status of patients with NMIBC has important implications for maintaining quality of life through stable urination and the administration of appropriate BCG treatment [10,21,22]. The quality of life of patients with non-muscle-invasive BC shows significant improvement in the fourth week after BCG induction [23].…”
Section: Discussionmentioning
confidence: 99%
“…BCG immunotherapy is the most successful adjuvant therapy for reducing the rate of NMIBC recurrence and progression (Kamat et al, 2015 ; Jiang and Redelman-Sidi, 2022 ; Unsworth-White et al, 2022 ). However, approximately 70% of patients undergoing BCG immunotherapy will develop lower urinary tract side effects characterized by sensory dysfunction including urinary urgency, urinary frequency, dysuria, and bladder pain that significantly impact wellbeing during treatment (Alexandroff et al, 1999 ; Brausi et al, 2014 ; Nouhaud et al, 2017 ; Danielsson et al, 2018 ; Unsworth-White et al, 2022 ; Yuen et al, 2022 ). Moreover, ~7–20% of patients are forced to discontinue BCG therapy due to the severity of their lower urinary tract symptoms (LUTS), significantly increasing the risk of cancer progression and reducing survival (van der Meijden et al, 2003 ; Brausi et al, 2014 ; Krajewski et al, 2018 ; Lebacle et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%